Analysis of CYP2C19 gene polymorphism and influencing factors of pharmacological response of clopidogrel in patients with cerebral infarction in Zhejiang, China - Mo, Yijun; Lu, Yao; Guo, Fei; Wu, Aihua; Weng, Yuesong (Frontiers in Cardiovascular Medicine, 2023)
Background Certain genetic and non-genetic factors may cause damaged platelet inhibition by clopidogrel. We aimed to determine the effect of cytochrome P4502C19 (CYP2C19) polymorphism, along with other clinical factors, on the platelet response to clopidogrel in patients with acute ischemic stroke (AIS). Methods A total of 214 patients with AIS receiving clopidogrel at a maintenance dose of 75 mg daily admitted to the Ningbo First Hospital between 1 January 2020, and 31 December 2021, were enrolled. Platelet aggregation analysis was performed to determine clopidogrel resistance. Quantitative real-time polymerase chain reaction (QRT-PCR) was used to determine CYP2C19 genotype. Other laboratory data on complete blood count and biochemical parameters were taken from patient medical files. Results Among the 214 AIS patients treated with clopidogrel in the Ningbo population, the incidence of clopidogrel resistance was approximately 43.9%, and the distribution of CYP2C19 genotypes was highest for CYP2C19(*1/*2) (43.0%), followed by CYP2C19 (*1/*1) (38.8%). The distribution of alleles *1, *2, *3, and *17 was 62.1, 32.5, 4.9, and 0.5%, respectively. A chi-squared test showed that the gene frequencies of alleles *2 and *3 were significantly higher in the clopidogrel-resistant group than in the clopidogrel-sensitive group (p < 0.001), and a Mann–Whitney U-test showed that high HCY levels were significantly correlated with clopidogrel resistance (p < 0.001). Multi-factor logistic regression analysis demonstrated that mutant heterozygous genotype [OR 2.893; 95% confidence interval (CI) 1.456–5.748; p = 0.002], mutant homozygous genotype (OR 4.741; 95% CI 1.828–12.298; p = 0.001), and high HCY levels (OR 1.209; 95% CI 1.072–1.362; p = 0.002) were significantly associated with clopidogrel resistance. Conclusion According to our results, carrying the CYP2C19*2/*3 allele and high HCY levels are independent risk factors for clopidogrel resistance after clopidogrel therapy in patients with AIS. These two factors should be considered prior to clopidogrel administration.